Enzo Catarsi, un pedagogista al plurale Scritti in suo ricordo - Sharmahd, Nima; FRESCHI, ENRICA; SILVA, Clara Maria (Libere carte, 2015)
The volume collects the papers of colleagues, friends and collaborators submitted during the conference "L'infanzia nella figura di Enzo Catarsi" ("Childhood in the figure of Enzo Catarsi), held in Florence on April 29, 2014. The conference was organised by the Department of Education and Psychology of the University of Florence, in collaboration with the Tuscany Region and the Istituto degli Innocenti, to remember the scholar Enzo Catarsi. With his death, the Department, the Municipalities of Tuscany, the community of pedagogists, the students and his closest collaborators are missing a reference figure and a personality of great scientific, cultural and human importance, with high educational ideals, great humanity, optimism, lightness and enthusiasm.